Pronunciation intelligibility of one Cameroonian English speaker to Brazilian listeners - Cruz, Neide Cesar; Ferraz D Ely, Raquel Carolina (Revista Horizontes de Linguistica Aplicada, 2016)
Abstract This study aims at answering the following questions: (1) which pronunciation features in the English spoken by one Cameroonian are likely to affect her speech intelligibility to Brazilian listeners? and (2) how far do these features diverge from the Brazilian way of pronouncing English? Speech samples containing pronunciation features which characterize the Cameroon English variety were presented to ten Brazilian listeners unfamiliar with this variety. They were asked to carry out two tasks: (1) to write down the samples; and (2) after having received the samples orthographic transcript, to explain the reasons for their difficulties in recognizing the words. The results reveal that words in the speech of the Cameroonian containing pronunciation features which diverge from the Brazilian way of pronouncing English were more unintelligible. Keywords: pronunciation intelligibility. Cameroon English. Brazilian listeners. Resumo Este estudo visa responder duas perguntas: (1) que aspectos de pronúncia no inglês falado por uma camaronesa afetam a inteligibilidade da sua fala para ouvintes brasileiros? e (2) até onde esses aspectos divergem da forma como brasileiros pronunciam inglês? Amostras contendo características de pronúncia do inglês camaronês foram apresentadas aos brasileiros, que foram solicitados a realizar duas tarefas: (1) escrever as amostras; e (2) após terem recebido a transcrição ortográfica das amostras, explicar as razões das suas dificuldades em reconhecer palavras. Os resultados revelam que vocábulos contendo aspetos de pronúncia que divergem da forma brasileira de pronunciar inglês foram mais ininteligíveis. Palavras-chave: inteligibilidade de pronúncia. inglês camaronês. ouvintes brasileiros.